Observations of a pre-merger shock in colliding clusters of galaxies - Gu, L.; Akamatsu, H.; Shimwell, T.W.; Intema, Huib; van Weeren, R.J.; de Gasperin, F.; Mernier, F.; Mao, J.; Urdampilleta, I.; de Plaa, J.; Parekh, V.; Röttgering, H.J.A.; et al. (2019)
Clusters of galaxies are the largest known gravitationally bound structures in the Universe. When clusters collide, they create merger shocks on cosmological scales, which transform most of the kinetic energy carried by the cluster gaseous halos into heat1–3. Observations of merger shocks provide key information on the merger dynamics, and enable insights into the formation and thermal history of the large-scale structures. Nearly all of the merger shocks are found in systems where the clusters have already collided4–12; knowledge of shocks in the pre-merger phase is a crucial missing ingredient13,14. Here, we report on the discovery of a unique shock in a cluster pair 1E 2216.0-0401 and 1E 2215.7-0404. The two clusters are observed at an early phase of major merger. Contrary to all the known merger shocks observed ubiquitously on merger axes, the new shock propagates outward along the equatorial plane of the merger. This discovery uncovers an important epoch in the formation of massive clusters, when the rapid approach of the cluster pair leads to strong compression of gas along the merger axis. Current theoretical models15,16 predict that the bulk of the shock energy might be dissipated outside the clusters, and eventually turn into heat of the pristine gas in the circum-cluster space.